2018
DOI: 10.1016/j.acra.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Natural Language Processing Rules-based and Machine-learning Systems to Identify Lumbar Spine Imaging Findings Related to Low Back Pain

Abstract: Our NLP system performed well in identifying the 26 lumbar spine findings, as benchmarked by reference-standard annotation by medical experts. Machine-learned models provided substantial gains in model sensitivity with slight loss of specificity, and overall higher AUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…We used machine learning natural language processing to extract imaging findings from radiology text reports. 20 We identified common imaging findings that are likely less clinically important (eg, disc bulge, disc space narrowing) vs likely more important (eg, moderate to severe spinal canal stenosis, nerve root compression (eAppendix 4 in Supplement 1 ). 1 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…We used machine learning natural language processing to extract imaging findings from radiology text reports. 20 We identified common imaging findings that are likely less clinically important (eg, disc bulge, disc space narrowing) vs likely more important (eg, moderate to severe spinal canal stenosis, nerve root compression (eAppendix 4 in Supplement 1 ). 1 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Utilizing classification techniques from radiology literature, new research is revealing the applicability of AI and ML algorithms to the analysis of spine imaging. One technique involves the use of ML models utilizing natural language processing to distinguish specific words and phrases from unstructured radiology reports in order to classify patients by imaging findings, as Tan et al 31 were able to do in a cohort of patients with low back pain. However, in more recent publications, other groups were able to utilize the imaging itself to detect and classify a variety of pathologies.…”
Section: Algorithms Have Been Ablementioning
confidence: 99%
“…40,42 These techniques can be adapted to assist spine surgeons via data extraction. For example, Tan et al 43 trained a model to identify information pertaining to low back pain (LBP) from lumbar spine imaging reports. Initially, the group determined 26 distinct findings to extract, such as annular fissure, scoliosis, disc protrusion, or spondylosis.…”
Section: Data Queryingmentioning
confidence: 99%
“…While both models were similar in specificity, the authors found that the ML model achieved greater sensitivity in the detection of "compound findings, " such as "nerve root displaced or compressed. " 43 Another example of NLP is a rules-based approach recently published by Wyles et al 44 for the analysis of total hip arthroplasty operative notes. Their algorithms captured information pertaining to operative approach, fixation method, and bearing surface.…”
Section: Data Queryingmentioning
confidence: 99%